2022
DOI: 10.1007/s00442-022-05292-8
|View full text |Cite
|
Sign up to set email alerts
|

Top-down and bottom-up forces explain patch utilization by two deer species and forest recruitment

Abstract: Ungulates play an important role in temperate systems. Through their feeding behaviour, they can respond to vegetation by selecting patches or modify vegetation composition by herbivory. The degree in which they interact with vegetation can either reinforce landscape heterogeneity by creating disturbance or reduce heterogeneity in case of overbrowsing. This study evaluates how bottom-up (patch quality, structure), top-down forces (hunting, distance to village, forest edge) and deer features (feeding type, abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…However, we must remember that the earliest stand stages in commercial forests represent only a part of the total ecosystem and deer browsing pressure may be lower at other stages of forest development. Although the threat posed by human hunters is thought to be the most important determinant of cervid responses in commercial forests during the day through the hunting season 36 , 60 62 , we have observed a pattern of changes in the distance from the forest edge selection by deer in the face of cursorial predators. We found that open-spaced centres of large-sized clearcuts and young forests, distant from older forest edges, seem to be the safest places for deer to reduce predation risk by wolves and to browse in northern Poland.…”
Section: Discussionmentioning
confidence: 67%
“…However, we must remember that the earliest stand stages in commercial forests represent only a part of the total ecosystem and deer browsing pressure may be lower at other stages of forest development. Although the threat posed by human hunters is thought to be the most important determinant of cervid responses in commercial forests during the day through the hunting season 36 , 60 62 , we have observed a pattern of changes in the distance from the forest edge selection by deer in the face of cursorial predators. We found that open-spaced centres of large-sized clearcuts and young forests, distant from older forest edges, seem to be the safest places for deer to reduce predation risk by wolves and to browse in northern Poland.…”
Section: Discussionmentioning
confidence: 67%
“…It is important to understand the fitness consequences of the fear of humans as an important stressor on other species for the management and conservation of these species (Darimont et al., 2015 ; Larson et al., 2016 ; Naidoo & Burton, 2020 ). In particular, it could enhance our understanding of the mechanisms that can result in trophic cascades (Chitwood et al., 2022 ), because large‐bodied ungulates can structure landscapes such as forests (Ramirez et al., 2018 , 2023 ), affecting forest‐related plant and animal species (Svenning et al., 2015 ). Large‐bodied ungulates may be expected to fear humans more strongly than other predators, such as wolves, thereby exhibiting strong responses to humans (see Ciuti et al., 2012 ; Crawford et al., 2022 ; Zbyryt et al., 2018 ), especially hunters (Cromsigt et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…An important finding was the difference in regeneration success between tree species: Scots pine showed the greatest expansion, whilst the rarer broadleaves showed limited expansion. This may partly reflect preferential browsing of broadleaves by deer (Ramirez et al, 2023), but is likely to be also a reflection of the lack of seed sources for rarer species and the requirement of some species for more open ground conditions to germinate successfully; future work as outlined above should help to elucidate this. Several authors have highlighted the merits of a spectrum of approaches to achieve woodland expansion (e.g.…”
Section: Caveats and Further Workmentioning
confidence: 99%